Outcome of children operated for congenital anorectal malformations: A prospective single center study - Saeid Aslanabadi; Hatef Alizadeh Aghdam; Masoud Jamshidi; Davoud Badebarin; Sina Zarrintan (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2018)
Introduction: Anorectal malformations (ARM) have an incidence of 1 in 5000 live births and affect male and female almost equally. Operative correction of pediatric ARM is of potential clinical interest; however, longterm outcome of patients in respect to probable complications requires precise follow up and surveillance. The aim of our study was to assess the outcomes of children undergoing surgical correction of ARMs. Materials and Methods: In a prospective follow-up study, we wanted to assess occurrence of incontinence, constipation, soiling, abdominal distension, diarrhea, stenosis, dilated sphincter and failure to thrive (FTT) in ARM patients. In addition, management of these conditions has been discussed. Reoperations have also been reviewed. The primary outcome of the study was determination of occurrence of incontinence at follow-up visits. Secondary outcomes were occurrence of constipation, anal stenosis, soiling, abdominal distension, dilated sphincter, diarrhea and FTT at followup visits. In addition, the decision of research team on patients at followup visits was considered as secondary outcomes. Results: Two hundred and ninety patients were studied. Of the study patients, 174 (60.4%) were boys and 114 (39.6%) were girls. Mean age of boys was 4.8 ± 2.0 years and mean age of girls was 5.0 ± 2.0 years. The mean follow-up period of our patients was 39.5 ± 29.1 months. During the study follow-up period, 63 patients (21.7%) had complications. The most common complication was constipation. It was present in 21 patients (33.3%). Soiling, incontinence, dilated sphincter, FTT, stenosis, abdominal distension and diarrhea were present in 21 (33.3%), 11 (17.5%), 9 (14.3%), 6 (9.5%), 6 (9.5%), 5 (7.9%), 3 (4.8%) and 2 (3.3%) patients respectively. Conclusion: We found that the most common complications following ARM surgery are constipation, soiling, incontinence, dilated sphincter, FTT, stenosis, distension and diarrhea. The overall complication rate was 21.7%. 7.2 % and 3.1% of study population experienced constipation and incontinency respectively. In 3.1% of the study population reoperation was required. We revealed that outcome of surgical correction of ARMs is considerably good and complication rates are acceptable. Continence rate was also acceptable.